As práticas de gestão da inovação em pequenos negócios conforme as diretrizes da Norma ABNT NBR ISO 56002:2020 : uma análise do Prêmio Inova Mato Grosso - Seixas, Patrícia Chaves Figueiredo (2023)
The challenge of systematizing innovation processes has been the object of study in business management literature and validates its importance for effective results in the generation of competitive advantage. Which makes it a strategic factor for business, regardless of business size. The ABNT NBR 56002:2020 technical standard appears as an alternative to expand the innovation capacity of businesses and create competitive advantage from the implementation of innovation management systems. This study aims to measure the maturity of innovation management practices applied by small businesses, with reference to the guidelines of the technical standard. The research was carried out by surveying the companies' innovation management practices and later measuring the maturity of the current systems in relation to the norm. The mapped data allowed identifying the existing gaps to reach the level of excellence proposed in the technical standard and still applying the importance X performance matrix (ANP analysis) being the IMPORTANCE, defined by the relevance of the clauses of the standard and THE PERFORMANCE, related to the company's capacity in applying it, it was possible to assess which clauses are complied with and which need improvement actions. Data analysis showed that the median level of maturity has a greater occurrence as the business size of the surveyed companies increases and even though for all sizes, most of the clauses in the ANP matrix are concentrated in the “improvements” decision zones and “excesses”, indicating possible paths for internal management.